Risk factors and microbiology of wound infections following cesarean delivery: Experience of a single institution - ILHAN, Gulsah; ATMACA, Fatma Ferda Verit; KAYA, Abdurrahman; ERGIN, Ahmet Hasan; Karasu, AYŞE FİLİZ; GÖKMEN KARASU, AYŞE FİLİZ; TURFAN, Mehtap (My University, 2016)
Aims: To determine the prevalence of wound infection following cesarean delivery, risk factors, common bacterial pathogens and their antibiotic sensitivity.